Clinical Predictors of Sodium Disturbance in Children Presenting with Acute Watery Diarrhea in a Tertiary Hospital of Bangladesh - Ara, Ferdous; Choudhury, Zabeen; Hasan, Syeda Humaida; Zebunnesa, Mosammat; Samad, Rasheda (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2023)
Background: Sodium disturbances, either hyponatremia or hypernatremia, are the most common electrolyte imbalance encountered in managing children with acute watery diarrhoea. Early diagnosis and prompt management of these conditions by identifying clinical predicting factors in diarrheal children under 5 years of age are critically essential to prevent deaths in such children, especially in resource-limited settings. Our study aimed to evaluate clinical predicting factors associated with sodium disturbance in children hospitalized with acute watery diarrhea. Materials and Methods: In this cross-sectional study, 121 children of 2 months to 5 years of age admitted in the Department of Pediatrics, Chittagong Medical College Hospital, Chattogram for acute watery diarrhea were included. Clinical features and sodium levels on admission were recorded. Children were grouped in hyponatremia (serum sodium <135mmol/l), hypernatremia (serum sodium >145mmol/l) and normonatremia (serum sodium 135–145mmol/l) and compared. Results: Of the 121 children, 18 (14.9%) were hyponatremic, 71 (58.7%) isonatraemic, and 32 (26.4%) hypernatraemic. Logistic regression analysis revealed that children who did not receive ORS before admission, had severe dehydration and lethargy on admission would be more likely to have hyponatremic dehydration. Children who were younger, received concentrated ORS, thirsty and had convulsions on admission would be more likely to have hypernatremic dehydration than children with isonatremia. Conclusion: The type of ORS used and age appears to be good predictors of sodium disturbance in children admitted with AWD. Chatt Maa Shi Hosp Med Coll J; Vol.22 (1); January 2023; Page 71-75